Carbon Black as a Modifier for a Cheap Carbon Paper Disposable Electrode for the Determination of Zaleplon in Synthetic Saliva - Aguirre-Quintana, M; Aguirre-Quintana, M; Navarro-Gajardo, F; Navarro-Gajardo, F; Pizarro-Reyes, J; Pizarro-Reyes, J; Flores-Vergara, E; Flores-Vergara, E (Springer Science and Business Media B.V., 2025)
The electrochemical determination of zaleplon, a sleep-inducing drug, is reported for the first time using a disposable electrochemical sensor based on carbon paper modified with carbon black via drop-coating. The electrochemical performance of the sensor was investigated using Square-Wave Adsorptive Voltammetry. The surface of the electrode was characterized through scanning electron microscopy, X-ray diffraction, and Raman spectroscopy. Nyquist plots from Electrochemical Impedance Spectroscopy reveal rough surface features in both electrodes, with more pronounced pore size effects observed for carbon paper than the modified electrode. Changes between both electrodes were attributed to differences in the capacitive and diffusive behavior of the analyte on each surface. Diffusional behavior was explained by macroscopic parameters, such as porosity and tortuosity. For the modified electrode, optimal chemical and electrochemical conditions were established for zaleplon detection, showing a linear range of 0.17 to 2.0 mM, a sensitivity of 0.086 mA mM−1, and a limit of detection and quantification of 0.019 and 0.079 mM, respectively. The addition of carbon black improved the pre-concentration capability of the sensor, enabling a new approach for rapid and sensitive zaleplon detection in oral fluids through a disposable electrode. © The Author(s), under exclusive licence to Springer Nature B.V. 2024.